The responsibility of the international community in preventing widespread human catastrophes in powerless governments - Mojtahedzade, Sepanta; Shiri, Yasaman (The journal of contemporary issues in business and government, 2021)
In the contemporary world, there are governments that are unable or unwilling to perform their functions as a government. In fact, they have fundamental problems in providing public services and establishing welfare and security in their territory, hence the economic and political dissatisfaction in this Territories lead to ongoing civil strife, which in turn provides a breeding ground for catastrophes such as genocide and war crimes. Given the imminence of widespread human catastrophes in these lands and the undeniable international consequences of these crises, the prevention of such catastrophes is one of the topics that should be given more attention because of course prevention is always better than treatment after a catastrophe. Unfortunately, this has been neglected in the field of international relations. Therefore, in the present article, with the help of research methods, while explaining the reasons for the need for effective action of the international community to prevent human catastrophes in the domestic territory of countries, we offer realistic and even practical solutions to prevent the occurrence of these problems. Let's take a step towards solving one of the most important challenges and obstacles in establishing global security.